Hubungan Beban Kerja, Pola Makan, Status Gizi terhadap Produktivitas Kerja pada Dokter dan Perawat Di RS XYZ Sumatera Selatan - Putu Ratih Wijayanthi; Viera Dzakiyyah Muthohharoh; Ory Laras Fitkarani; Innocentius Bernarto (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
The purpose of the study was to determine the relationship between workload, diet, nutritional status and work stress with work productivity in doctors and nurses of XYZ Hospital in South Sumatra. The research method used is quantitative using Structural Equation Modeling (SEM) Partial Least Square (PLS), using SMART PLS 4.0 Software. The sample used in this study was 159 doctors and nurses. Data collection tools in the form of questionnaires about workload, diet, nutritional status, work stress and work productivity. The results showed that workload, diet, nutritional status had a positive effect on work productivity in doctors and nurses at XYZ Hospital in South Sumatra.